2002
DOI: 10.1103/physrevd.65.056001
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic effects in cold magnetized nucleons and electrons with anomalous magnetic moments

Abstract: A model of a degenerate neutron gas in chemical equilibrium with a background of degenerate electrons and protons in a constant uniform ultrastrong magnetic field is applied to describe the state of matter in the cores of strongly magnetized neutron stars. Expressions for the thermodynamic quantities are obtained including the anomalous magnetic moments of the fermions. It is shown that ͑1͒ the inclusion of the anomalous magnetic moments of charged fermions leads to nonperiodic magnetic oscillations of their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…Recent observations of soft gamma repeaters (SGRs) and anomalous X-ray pulsars (AXPs) have suggested that the surface magnetic field of young neutron stars could be of order 10 14 − 10 15 G [1]. On the other hand, it is estimated that the interior field in neutron stars may be as large as 10 18 G [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations of soft gamma repeaters (SGRs) and anomalous X-ray pulsars (AXPs) have suggested that the surface magnetic field of young neutron stars could be of order 10 14 − 10 15 G [1]. On the other hand, it is estimated that the interior field in neutron stars may be as large as 10 18 G [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is estimated that the interior field in neutron stars may be as large as 10 18 G [2,3]. Motivated by the existence of strong magnetic fields in neutron stars, theoretical studies on the effect of extremely large fields on dense matter and neutron stars have been carried out by many authors [3,4,5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that strong magnetic fields populate the vast majority of the astrophysical compact objects and that they can significantly affect several properties of the star have served as motivation for many works focused on the study of the EoS of magnetized neutron stars, without considering , or considering the magnetic-field interaction with the particle anomalous-magnetic-moment [88,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113]. An important characteristic is that the EoS in a uniform magnetic field becomes anisotropic, with different pressures along the field and transverse to it [73,94,98].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, when investigating the field effects in the EoS, it is consistent to take a magnetic field that is locally constant and uniform. This is the reason why such an approximation has been systematically used in all the previous works on magnetized nuclear [1,20,25,28,29,34,35,72,79,87,115,121,124,136,140,143] and quark matter [32,33,74,104,105,120].…”
Section: Equation Of State Of the Mcfl Phasementioning
confidence: 99%